\(4\left(x-3\right)^2-2x\left(x-3\right)\)

Đặt nhân tử chung đa thức trên

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

19 tháng 9 2017

4(x-3)2-2x(x-3)

=(x-3)(4x-12-2x)

=(x-3)(2x-12)

=(x-3).2(x-6)

=2(x-3)(x-6)

19 tháng 9 2017

 4(x-3)2-2x(x-3)

=2(x-3)(2x-6-x)

=2(x-3)(x-6)

10 tháng 10 2018

a)4y(x-1)-(x+1)=4y(x-1)-(X-1)

   =(x-1) (4y-1)

b)\(\left(x-3\right)^3\)+3-x=(x-3)^3+(x-3)

=x-3 (x-3)^2

HOK TỐT K NHA

29 tháng 6 2018

\(1,=\left(x+1\right)\left(x^2+2x\right)=\left(x+1\right)x\left(x+2\right)\)

\(2,=x\left(2x-3\right)+2\left(2x-3\right)=\left(2x-3\right)\left(x+2\right)\)

\(3,=3x\left(x-1\right)-\left(x-1\right)=\left(x-1\right)\left(3x-1\right)\)

\(4,=2x\left(x-y\right)-6\left(x-y\right)=\left(x-y\right)\left(2x-6\right)=\left(x-y\right)2\left(x-3\right)\)

\(5,=4x\left(x+3\right)\)

2 tháng 11 2016

a)x4+2x3+5x2+4x-12

=(x4+2x3+x2)+(4x2+4x)-12

=(x2+x)2+4(x2+x)-12

Đặt t=x2+x

=t2+4t-12=(t-2)(t+6)

=(x2+x-2)(x2+x+6)

=(x-1)(x+2)(x2+x+6)

b)(x+1)(x+2)(x+3)(x+4)+1

=(x2+5x+4)(x2+5x+6)+1

Đặt x2+5x+4=t

t(t+2)+1=t2+2t+1

=(t+1)2=(x2+5x+4+1)2

=(x2+5x+5)2

c)(x+1)(x+3)(x+5)(x+7)+15

=(x2+8x+7)(x2+8x+15)+15

Đặt t=x2+8x+7

t(t+8)+15=(t+3)(t+5)

=(x2+8x+7+3)(x2+8x+7+5)

=(x2+8x+10)(x+2)(x+6)

d)(x+1)(x+2)(x+3)(x+4)-24

=(x2+5x+4)(x2+5x+6)-24

Đặt t=x2+5x+4 

t(t+2)-24=(t-4)(t+6)

=(x2+5x+4-4)(x2+5x+4+6)

=x(x+5)(x2+5x+10)

10 tháng 10 2018

a, 4y(x-1)-(1-x)

=(x-1)(4y+1)

b,3x(z+2)+5(-x-2)

=3x(z+2)-5(x+2)

=(z+2)(3x-5)

12 tháng 10 2019

=8x3y + z3y + 8x3z -2xz3 - y3(z +2x)= y(8x3+z3) +2xz(4x2-z2) - y3(2x+z) = y(2x+z)(4x2 - 2xz + z2) +2xz(2x+z)(2x-z) - y3(2x+z)

=(2x+z)(4x2y -2xyz + z2y + 4x2z -2xz2 - y3) = (2x+z)( 4x2y+ 4x2z - 2xyx- 2xz2 +z2y - y3) = (2x+z)[ 4x2(y+z) -2xz(y+z) + y(z+y)(z-y)]

= (2x+z)(y+z)( 4x2- 2xz +yz- y2) = (2x+z)(y+z)(4x2 - y2 -2xz + yz) = (2x+z)(y+z)[(2x-y)(2x+y) - z(2x-y)] 

= (2x+y)(y+z)(2x-y)(2x+y-z)

11 tháng 9 2018

Đặt x^2+2x=t =>3t^2-2t-1=3t^2-3t+t-1=3t(t-1)+(t-1)=(t-1)(3t+1)

=>(x^2+2x-1)(3x^2+6x+1)

16 tháng 10 2020

(x - 5)2 - 4(x - 3)2 + 2(2x - 1)(x - 5) + (2x - 1)2

= [(x - 5)2 + 2(2x - 1)(x - 5) + (2x - 1)2) - [2(x - 3)]2

= (x - 5 + 2x - 1)2 - (2x - 6)2

= (3x - 6)2 - (2x - 6)2

= (3x - 6 - 2x + 6)(3x - 6 + 2x - 6) = x(5x - 12)

16 tháng 10 2020

( x - 5 )2 - 4( x - 3 )2 + 2( 2x - 1 )( x - 5 ) + ( 2x - 1 )2

= [ ( x - 5 )2 + 2( 2x - 1 )( x - 5 ) + ( 2x - 1 )2 ] - 22( x - 3 )2

= ( x - 5 + 2x - 1 )2 - ( 2x - 6 )2

= ( 3x - 6 )2 - ( 2x - 6 )2

= ( 3x - 6 - 2x + 6 )( 3x - 6 + 2x - 6 )

= x( 5x - 12 )